2021
DOI: 10.1302/1863-2548.15.200157
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage medial plateau elevation and metaphyseal osteotomies in advanced-stage Blount's disease: A new technique

Abstract: Purpose Surgical treatment in advanced-stage infantile Blount’s disease with medial plateau (MP) depression is challenging. Several osteotomies and fixation methods have been described with no established benchmark. We conducted this study to evaluate the efficacy and safety of a new single-stage technique for acute medial condyle elevation and metaphyseal osteotomies with internal fixation. Methods A prospective case series of 19 consecutive patients (21 knees) with severe infantile Blount’s disease underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The most featured technique featured in papers reviewed employed proximal tibial osteotomy [ 1 , 4 , 5 , [7] , [8] , [9] , 12 , 13 ] with different location of surgical interventions, namely intra-epiphyseal [ 11 ], metaphyseal [ [14] , [15] , [16] ], and subperiosteal [ 17 ] sites. At least three procedures described were performed as double osteotomy in a single surgery [ 10 , 17 , 18 ], and at least two described grafting fibular fragments into tibial openings [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most featured technique featured in papers reviewed employed proximal tibial osteotomy [ 1 , 4 , 5 , [7] , [8] , [9] , 12 , 13 ] with different location of surgical interventions, namely intra-epiphyseal [ 11 ], metaphyseal [ [14] , [15] , [16] ], and subperiosteal [ 17 ] sites. At least three procedures described were performed as double osteotomy in a single surgery [ 10 , 17 , 18 ], and at least two described grafting fibular fragments into tibial openings [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review saw majority of the reported osteotomies were stabilized using internal fixations, with minimal screws [ 12 ], plates and screws [ 1 , 9 , 13 , 15 , 16 ], and K-wires [ 4 , 17 , 18 ]. The rest of external fixations described mainly used the hexapod rings resembling Ilizarov apparatus [ 5 , 14 ] and one considered using mono-lateral L-shaped pins to achieve gradual correction [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Children 2021, 8, x FOR PEER REVIEW technique using a gigli saw to perform the osteotomy to avoid the risk of intra fracture and medial condyle displacement [84]. The open-wedge defect is bone and the osteotomy stabilized with internal or external fixation.…”
Section: Hemi-plateau Elevation Osteotomymentioning
confidence: 99%
“…Increased posterior depression can be differentially corrected with rotation in the sagittal plane. Barka et al recently described an "inside-out" technique using a gigli saw to perform the osteotomy to avoid the risk of intra-articular fracture and medial condyle displacement [ 84 ]. The open-wedge defect is bone-grafted, and the osteotomy stabilized with internal or external fixation.…”
Section: Hemi-plateau Elevation Osteotomymentioning
confidence: 99%
“…However, innovation does not necessary mean a description a new surgical technique or an introduction of a new molecule or drug. This represents one aspect of research novelty only [30].…”
Section: Demonstrating Novelty In Researchmentioning
confidence: 99%